Association of psychosocial factors with leukocyte telomere length among African Americans in the Jackson Heart Study. (21st December 2018) - Jordan, Christina D.; Glover, LáShauntá M.; Gao, Yan; Musani, Solomon K.; Mwasongwe, Stanford; Wilson, James G.; Reiner, Alex; Diez‐Roux, Ana; Sims, Mario
Abstract: Leukocyte telomere length (LTL) is a biomarker of cellular aging. African Americans report more stress than other groups; however, the association of psychosocial stressors with biological aging among African Americans remains unclear. The current study evaluated the association of psychosocial factors (negative affect and stressors) with LTL in a large sample of African American men and women ( n = 2, 516) from the Jackson Heart Study. Using multivariable linear regression, we examined the sex‐specific associations of psychosocial factors (cynical distrust, anger in and out, depressive symptoms, negative affect summary scores, global stress, weekly stress, major life events, and stress summary scores) with LTL. Model 1 adjusted for demographics and education. Model 2 adjusted for model 1, smoking, alcohol intake, physical activity, diabetes, hypertension, and high‐sensitivity C‐reactive protein. Among women, high (vs. low) cynical distrust was associated with shorter mean LTL in model 1 ( b = −0.12; p = 0.039). Additionally, high (vs. low) anger out and expressed negative affect summary scores were associated with shorter LTL among women after full adjustment ( b = −0.13; p = 0.011; b = −0.12, p = 0.031, respectively). High levels of cynical distrust, anger out, and negative affect summary scores may be risk factors for shorter LTL, particularly among African‐American women.